Anne of Green Gables - Book 1 - (Lucy Maud); Montgomery, L. M.; 1874-1942. (Philadelphia, PA, 1993)
Anne, an eleven-year-old orphan, is sent by mistake to live with a lonely middle-aged brother and sister on a Prince Edward Island farm and proceeds to make an indelible impression on everyone around her.
With an excerpt from the author's journal.
Keywords: Orphans; Fiction; Friendship; Fiction; Country life; Fiction; Prince Edward Island; Prince Edward Island; Fiction